When the world was ours - Kessler, Liz (Aladdin, 2022)
Leo, Elsa, and Max are best friends who live in Vienna in 1936. But with Hitler's rise to power, the three are torn apart. Elsa's family moves to Czechoslovakia seeking asylum, Leo's father is imprisoned and his family tries to get out of Austria to a safer country, and Max's father, an SS officer, moves his family to Munich while he works at Dachau. Eventually, the three will be reunited in way they never could have imagined.